Chikungunya infection in pregnancy – reassuring maternal and perinatal outcomes: a retrospective observational study. (19th November 2020) - Foeller, ME; Nosrat, C; Krystosik, A; Noel, T; Gérardin, P; Cudjoe, N; Mapp‐Alexander, V; Mitchell, G; Macpherson, C; Waechter, R; LaBeaud, AD
Abstract : Objective: To evaluate pregnancy and neonatal outcomes, disease severity, and mother‐to‐child transmission of pregnant women with Chikungunya infection (CHIKV). Design: Retrospective observational study. Setting: Grenada. Population: Women who gave birth during a Chikungunya outbreak between January 2014 and September 2015 were eligible. Methods: This descriptive study investigated 731 mother‐infant pairs who gave birth during a CHIKV outbreak. Women and infants underwent serological testing for CHIKV by ELISA. Main outcome measures: Primary outcomes: composite pregnancy complication (abruption, vaginal bleeding, preterm labour/cervical incompetence, cesarean delivery for fetal distress/abruption/placental abnormality or delivery for fetal distress) and composite neonatal morbidity. Results: Of 416 mother‐infant pairs, 150 (36%) had CHIKV during pregnancy, 135 (33%) had never had CHIKV, and 131 (31%) had CHIKV outside of pregnancy. Mean duration of joint pain was shorter among women infected during pregnancy (μ = 898 days, σ = 277 days) compared with infections outside of pregnancy (μ = 1064 days, σ = 244 days) ( P  < 0.0001). Rates of pregnancy complications (RR = 0.76, P  = 0.599), intrapartum complications (RR = 1.50, P  = 0.633), and neonatal outcomes were otherwise similar. Possible mother‐to‐child transmission occurred in two (1.3%) mother‐infant pairs and two of eight intrapartum infections (25%). Conclusion: CHIKV infection during pregnancy may be protective against long‐term joint pain sequelae that are often associated with acute CHIKV infection. Infection during pregnancy did not appear to pose a risk for pregnancy complications or neonatal health, but maternal infection just prior to delivery might have increased risk of mother‐to‐child transmission of CHIKV. Tweetable abstract: Chikungunya infection did not increase risk of pregnancy complications or adverse neonatal outcomes, unless infection was just prior to delivery. Tweetable abstract: Chikungunya infection did not increase risk of pregnancy complications or adverse neonatal outcomes, unless infection was just prior to delivery.